Chinese student migration, social networking, and local engagement in the UK - Wu, Bin (Brill Academic Publishers, 2016)
The unprecedented growth in the number of Chinese international students since the twenty-first century raises questions about their links to and impact on local communities in host countries. Viewing Chinese students as an important part of diasporic Chinese community, this paper sheds new light on Chinese students’ social networking with different groups internally and externally, both Chinese and non-Chinese, on campus or in the wider community. Many questions arise: What is the contribution of Chinese students to the growth and transformation of diasporic Chinese communities in major destinations? What is the scope of their social networking and what are their functions in regard to Chinese community cohesion and integration? What are the differences between Chinese students and local residents and between Chinese students from mainland China and those from Hong Kong and Singapore in terms of network building and local engagement? The above questions are addressed by a combination of official data analysis and a questionnaire survey conducted in Nottingham. The evidence suggests a correlation between the local engagement of Chinese students in the wider community and their social networking, which offers a key to understand the new momentum for the transformation of diasporic Chinese community in major HE destinations. Theoretical and policy implications are discussed.